Case report: Complete clinical remission of feline progressive histiocytosis after multimodal treatment including electrochemotherapy - Sena, Bruna Voltolin de; Turquete, Paula Baêta da Silva Rios; Pimentel, Pedro Antônio Bronhara; Almeida, Isabella Oliveira; Lavalle, Gleidice Eunice; Nakagaki, Karen Yumi Ribeiro; Giuliano, Antonio; Paes, Paulo Ricardo de Oliveira; Horta, Rodrigo dos Santos (Frontiers in Veterinary Science, 2024)
Feline histiocytic diseases are uncommon and rarely reported. Feline progressive histiocytosis (FPH) is the most common histiocytic disease in cats, typically, affecting middle-old age animals. The most common presentation is the cutaneous form with solitary or multiple cutaneous nodules. A female, mixed-breed 6-year-old cat was presented with a 9-month history of a nodule in the nasal planum, diagnosed by histopathology with histiocytic proliferation. At the time of diagnosis new nodules were discovered on the lower lip, digit, and two lesions in the tail region, with the largest measuring 1.5 cm. Supplementary immunohistochemistry, showed immunolabelling for Iba-1 that in combination with the clinical course of the disease, confirmed the diagnosis of FPH. No response to chemotherapy treatment with lomustine alternated with doxorubicin was achieved. Toceranib phosphate, resulted in a transient response and, stable disease for a short period (6 weeks). Electrochemotherapy with bleomycin was initiated and resulted in partial remission. Later on chlorambucil was also started. Ultimately, the combination of all three treatments led to a complete response and disappearance of all the 1 lesions. FPH is considered a disease resistant to various treatments, and effective treatments have not been reported. In this case report, we describe a successful multimodal therapeutic approach that resulted in complete resolution of the FPH and long-term survival (460 days without external lesions at the time of death). Further studies are necessary to confirm the efficacy of this therapeutic approach.